Inter-agency analysis of EU specialised administrative services - Kirlappos, Andreas (Central European Public Administration Review, 2024)
Purpose: The Republic of Cyprus is a small EU member state whose domestic administrative structures replicate an enduring tradition of centralisation. This study employs three Europeanisation processes to investigate the influence of European integration on EU specialised administrative services and explain possible differentiations. Design: This research employs two methodological tools: a literature review of domestic and international literature on Europeanisation and historical institutionalism, and a field study employing interviews and questionnaires with public servants working within these services. Findings: The results suggest that while Cyprus’s EU membership has played a significant role in the Europeanisation of domestic administrative structures, this process remains incomplete due to historical continuities from previous eras. These have an enduring impact on formal andinformal institutions, diminishing the role of the examined services and constraining the behaviour of public servants. Academic contribution to the field: This study offers a theoretical contribution by providing a comprehensive understanding of moderate Europeanisation effects on EU specialised structures within the Cypriot administrative framework. It also highlights the consequences of historical continuities manifested through formal and informal institutional constraints (endogenous characteristics, tangible factors, and conservative attitudes) and their adverse effects on the promotion of institutional and administrative change. Practical implications: The research findings underscore the relevance for future studies. They are particularly pertinent in assessing the effects of European integration and administrative change in other EU member states sharing similar historical experiences with Cyprus, such as Greece and Malta. Originality/Significance/Value: This study is innovative in its focus on specific administrative actors in Cyprus whose role has not been examined so far. It sheds light on tangible and intangible factors that may influence the promotion of institutional and administrative change.
Keywords: domestic administrative structures; EU; European Union; Europeanisation; evropeizacija; Evropska unija; historical institutionalism; notranje upravne strukture; Republic of Cyprus; Republika Ciper; zgodovinski institucionalizem